Faktor-Faktor yang Berhubungan dengan Kepemilikan Saluran Pembuangan Air Limbah Rumah Tangga - Fera Meliyanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2018)
Scope of sewerage for Belimbing Village in 2014 was eligible amount to 30,71 percent of 127 families (KK) having Sewers Waste (SPAL), in 2015 amounted to 35,67 percent of the 127 families who have SPAL, and in 2016 amounted to 37,71 percent of the 127 families who have SPAL. Based on the coverage of data, the number of households that have SPAL in Belimbing village is still low. The purpose of this study was to determine the factors associated with the ownership of sewerage households. The research is descriptive analytic research with a cross-sectional design. This study population around the head of the family in the village of Belimbing amounted to 127 households. Samples using total sampling. Place of research conducted in the District Supplied Belimbing Village Ogan Komering Ulu. Data were analyzed by univariate and bivariate analysis. The statistical test using chi-square test. From the results, there was a significant relationship between knowledge with SPAL ownership with p-value 0,001; no significant association of education with SPAL ownership with p-value 0,001; there is a significant relationship between the length of working with SPAL ownership with p-value 0,002; there is a significant relationship between earnings by ownership SPAL with p-value of 0,015.